Productive and reproductive performance of indigenous buffaloes in four selected upazillas under Mymensingh district of Bangladesh - Karim, Mohammad Rezaul; Habib, Raihan; Hossain, Mohammad Imam; Wadud, Abdul (Asian Journal of Medical and Biological Research, 2023)
The present study aimed to examine the productive and reproductive performance of Indigenous buffaloes in the Mymensingh district of Bangladesh. Buffalo husbandry plays a crucial role in the livelihoods of numerous farmers across various upazilas in Mymensingh. A total of 100 indigenous buffaloes were selected for the study, representing four upazilas: Trishal, Haluaghat, Muktagachha, and Sadar upazilla in Mymensingh district. The findings of this study revealed that the average lactation length of indigenous buffaloes was 273.04±4.75 days. Furthermore, the average milk yield of indigenous buffaloes was measured at 2.33±0.77 litres. The average birth weight, gestation period, age at first calving, calving interval, and post-partum heat period for indigenous buffaloes were observed to be 19.44±3.24 kg, 313.04±6.40 days, 52.53±3.10 months, 558.43±60.05 days, and 142.33±29.32 days, respectively. Based on the results obtained from all the parameters studied, it can be concluded that the productive and reproductive performance of Indigenous buffaloes in the Trishal upazilla surpassed that of the other three upazilas. Asian J. Med. Biol. Res. 2023, 9 (2), 30-37